2008
DOI: 10.1111/j.1753-4887.2008.00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Update on alpha-linolenic acid

Abstract: Consumption of omega 3 fatty acids is known to have health benefits. For many years, the importance of the only member of the omega 3 family considered to be essential, alpha-linolenic acid (ALA), has been overlooked. Current research indicates that ALA, along with its longer chain metabolites, may play an important role in many physiological functions. Potential benefits of ALA include cardioprotective effects, modulation of the inflammatory response, and a positive impact on both central nervous system funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
110
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(116 citation statements)
references
References 45 publications
2
110
0
4
Order By: Relevance
“…Linoleic acid (LA) and α-linolenic acid (ALA) are essential fatty acids because they cannot be synthesized by the human body (Stark et al, 2008), and they are the major n-6 and n-3 fatty acids in milk. Several studies indicate that ALA has cardio-protective effects (Albert et al, 2005;Djoussé et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Linoleic acid (LA) and α-linolenic acid (ALA) are essential fatty acids because they cannot be synthesized by the human body (Stark et al, 2008), and they are the major n-6 and n-3 fatty acids in milk. Several studies indicate that ALA has cardio-protective effects (Albert et al, 2005;Djoussé et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely accepted that α-linolenic acid can promote human health, especially reducing the risk of cardiovascular diseases (de Lorgeril et al 1994). It is considered to relate with the fluidity and physiological functions of cell membrane, signal transduction and gene expressions in living cells (Stark et al 2008). Moreover, it is also known that the n-6/n-3 ratio of diets is more essential than total intake of each fatty acid, since the signaling cascades of n-6 and n-3 feedback to each other to maintain homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been noted that linoleic acid intake has increased substantially in Western societies (18) , which is of concern because of the shared metabolic pathways of both the n-3 and n-6 PUFA and the resulting competition for metabolite production (19) , which has had an impact on the efficiency of conversion of ALA to EPA. It has been concluded that the concept of n-6 : n-3 is not as useful as considering the impact of actual low consumption of LC n-3 PUFA (20) . In either case, the concurrent increase in n-6 consumption and decrease in n-3 consumption deserves attention, including consideration of the options for increased supply of LC n-3 PUFA.…”
Section: Proceedings Of the Nutrition Societymentioning
confidence: 99%